ORGANIZATIONAL RESTRUCTURING AND CORPORATE PERFORMANCE IN PUBLIC SECTOR ORGANIZATIONS IN RIVERS STATE (American Journal of Pedagogical and Educational Research, 2025)
This paper investigates how key literary devices in Dan Brown’s The Da Vinci Code – such as metaphors, symbolism, allusions, idioms, and wordplay – are rendered in the original English and in the canonical Russian and Uzbek translations. We conduct a comparative stylistic analysis of representative examples (e.g. idiomatic phrases and symbolic references), examining the translation strategies used and the challenges posed by linguistic and cultural differences. Findings show that both Russian and Uzbek translators employ extensive paraphrase and explanatory techniques to convey Brown’s colloquial, reference-heavy style. Idioms are often translated periphrastically or omitted, and complex concepts like the “Holy Grail” require cultural adaptation. Wordplay (e.g. the famous Latin anagram “O Draconian devil! Oh, lame saint!”) cannot be preserved and is typically glossed or left in the source language. The analysis underscores the tension between preserving authorial effect and ensuring comprehension for target readers, reflecting theories of functional equivalence and culturally-aware transThe study investigated the effect of organizational restructuring on corporate performance in public sector organizations in Rivers State. The study specifically examined how restructuring frequency, implementation quality, and communication strategies influence operational efficiency, service delivery, and overall organizational effectiveness. Data were collected from annual reports, internal performance records, and official documents of selected public sector organizations through a desk survey method. Ordinary least squares of multiple regression models were used to determine the effect of restructuring practices, while correlation analysis was employed to examine the relationship between organizational restructuring and corporate performance. The results revealed that well-planned and effectively implemented restructuring has a significant effect on corporate performance in public sector organizations. The findings further indicated a strong positive relationship between the quality of restructuring implementation and improved efficiency, stakeholder satisfaction, and service delivery outcomes. It was recommended that public sector organizations should adopt comprehensive restructuring frameworks, ensure clear communication of changes, and provide training to support staff adaptation and engagement. This would enhance operational efficiency, service delivery, and overall organizational performance in Rivers State.lation practice.